Age-Related Long-Term Functional Results after Riboflavin UV A Corneal Cross-Linking. (4th August 2011) - Caporossi, Aldo; Mazzotta, Cosimo; Baiocchi, Stefano; Caporossi, Tomaso; Denaro, Rosario
Abstract : Purpose . To report a comparative prospective long-term functional analysis after Riboflavin UV A corneal cross-linking (CXL) in three different age groups of patients affected by progressive keratoconus (KC). Methods . Functional analysis comprised paediatric patients (≤18 years) included 152 eyes (29.5%); intermediate group (19–26 years) 286 eyes (55.4%), and adults (≥27 years) 78 eyes (15.1%). CXL was performed according to the Siena protocol by using the Vega CBM (Caporossi-Baiocchi-Mazzotta) X linker (CSO, Florence, Italy) at Siena University by the same authors. Pre- and post-op examinations included UCVA, BSCVA, corneal topography, and surface aberrometry (CSO Eye Top, Florence, Italy), at 48 months followup. Results . At 48 months followup paediatrics, intermediate, and adult patients showed a mean gain in UCVA of +0.2, +0.14 and +0.12 Snellen lines. BSCVA gained by a mean of +0.21, +0.2, and +0.1 Snellen lines. K max was reduced by a mean value of −0.9 D, −0.6 D, and −0.5 D, respectively. Coma values improved by a mean of −0.45 μm, −0.91 μm, and −0.19 μm, respectively. Treatment ensured a long-term keratoconus stabilization in over 90% of treated patients. Conclusion . According to our long-term comparative results, epithelium-off Riboflavin UV A cross-linking should be the first choice therapy of progressive KC, particularly in paediatric age and patients under 26 years.